DESIGN, SYNTHESIS, MOLECULAR DOCKING, AND EVALUATION OF CHROMONE BASED TETRAZOLE DERIVATIVES - CHOPRA, ANUJA; SINGH, LAKHWINDER; VK, KAPOOR; DHINGRA, RICHA; DHINGRA, NEELIMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of this research work was to design, synthesize, study the molecular docking, and evaluate the antimicrobial activity of some novel substituted 2-(Phenylamino)-3-(1H-tetrazol-5-yl)-4H-chromen-4-one derivatives (12a-h). Methods: In the present work, 3-Formylchromones were transformed into pharmacologically active substituted 2-(Phenylamino)-3-(1H-tetrazol-5- yl)-4H-chromen-4-one derivatives (12a-h) through a multistep reaction. Initially, synthesis of the substituted 4-Oxo-2-(phenylamino)-4H-chromone-3- carbaldehydes (9a-h) was carried out using substituted acetophenones (6a-h) as starting material and by employing an earlier reported method (1,3-dipolar cycloaddition reaction). Then, these synthesized compounds were converted into respective oximes (10a-h).The obtained oximes (10a-h) were further converted into nitriles (11a-h) which were finally subjected to concerted cycloaddition through stepwise addition of neutral or anionic azide species to furnish final substituted 2-(Phenylamino)-3-(1H-tetrazol-5-yl)-4H-chromen-4-one derivatives (12a-h). All the newly synthesized compounds (12a-h) and a reference compound (ciprofloxacin) were docked into the active site of TyrRS (PDB: 1JIK) by means of the BioPredicta module of VLife MDS. The synthesized compounds (12a-h) were also evaluated in vitro for their antibacterial (against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli bacterial stains) and antifungal activities (against Aspergillus niger and Candida albicans fungal strains) using Zone of Inhibition method. Results: The formation of substituted 2-(Phenylamino)-3-(1H-tetrazol-5-yl)-4H-chromen-4-one derivatives (12a-h) was confirmed through their spectral analysis, that is, 1H-NMR, 13C-NMR, and Mass spectroscopy. During docking study, the recorded molecular binding interactions revealed that all the newly synthesized compounds (12a-h) interacted well with binding site of the enzyme. The synthesized compounds were also evaluated in vitro for their antibacterial (against S. aureus, B. subtilis, P. aeruginosa, and E. coli bacterial stains) and antifungal activities (against A. niger and C. albicans fungal strains). All the synthesized compounds exhibited moderate-to-potent antimicrobial activities. Conclusions: All the synthesized compounds exhibited moderate-to-potent antimicrobial activity.